Ciliated Foregut Cyst of the Pancreas. Issue 2 (1998) - Munshi, Imtiaz A.; Parra-Davila, Eduardo; Casillas, Victor J.; Sleeman, Danny; Levi, Joé U.
Abstract : Cystic lesions of the pancreas are relatively uncommon. We describe the case of a young man with a complex cystic mass located within the head of the pancreas. The patient underwent exploration with resection of the mass. Pathology revealed a ciliated epithelial cyst, a rare cystic lesion of the pancreas.